Comparative Evaluation of the Effects of Legacy and New Generation Perfluoralkyl Substances (PFAS) on Thyroid Cells In Vitro - De Toni, Luca; Di Nisio, Andrea; Rocca, Maria Santa; Pedrucci, Federica; Garolla, Andrea; Dall’Acqua, Stefano; Guidolin, Diego; Ferlin, Alberto; Foresta, Carlo (Frontiers in Endocrinology, 2022)
Background: Per- and poly-fluorinated alkyl substances (PFAS) are environment-persitent emerging endocrine disrupting chemicals raising health concerns worldwide. Exposure to PFAS has been associated with alteration of thyroid hormones balancing. However, available studies addressing the cell mechanism underlying thyroid disrupting feature of legacy PFAS, such as perfluoro-octanoic acid (PFOA) and perfluoro-octane-sulfonic acid (PFOS), and the new generation substitutes, such as C6O4, are still lacking. In this study, the potential disrupting effect of PFOA, PFOS and C6O4 on a murine thyroid cell model was assessed. Methods: Rat FRTL-5 cell line was used as normal thyroid follicular cell model. Cell iodide-uptake induced by thyroid stimulating hormone (TSH) was used to assess the functional impact of PFAS exposure on cell function. Tetrazolium salt-based cell viability assay and merocyanine 540-based cell staining were used to address the possible involvement of cell toxicity and membrane biophysical properties on altered cell function. The possible direct interaction of PFAS with TSH-receptor (TSH-R) were investigated by computer-based molecular docking and analysis of molecular dynamics. Evaluation of intracellular cAMP levels and gene expression analysis were used to validate the direct impairment of TSH-R-mediated downstream events upon PFAS exposure. Results: Differently from PFOS or C6O4, exposure to PFOA at concentration ≥ 10 ng/mL was associated with a significant impairment of the iodide uptake upon TSH stimulation (respectively: basal 100.0±19.0%, CTRL + TSH 188.9±7.8%, PFOA 10 ng/mL + TSH 120.4±20.9%, p= 0.030 vs CTRL + TSH; PFOA 100 ng/mL + TSH 115,6±12,3% p= 0.017 vs CTRL + TSH). No impairment of cell viability or membrane stability was observed. Computational analysis showed a possible direct differential interaction of C6O4, PFOA and PFOS on a same binding site of the extracellular domain of TSH-R. Finally, exposure to PFOA was associated to a significant reduction of downstream intracellular cAMP levels and both sodium-iodide transporter and thyroperoxidase gene expression upon TSH-R stimulation. Conclusions: Our data suggest that legacy and new generation PFAS can differentially influence TSH dependent signalling pathways through the direct interaction with TSH-R.